Time-dependent coupling of electron energy distribution function, vibrational kinetics of the asymmetric mode of CO2 and dissociation, ionization and electronic excitation kinetics under discharge and post-discharge conditions. (2nd November 2016) - Pietanza, L D; Colonna, G; D'Ammando, G; Capitelli, M
Abstract: A time-dependent self-consistent model based on the coupling of the Boltzmann equation for the electron energy distribution function (EEDF) with the non-equilibrium vibrational kinetics of the asymmetric mode, as well as a simplified global model, have been implemented for a pure CO2 plasma. The simplified time-dependent global model takes into account dissociation and ionization as well as the reverse of these processes. It also takes into account the excitation/de-excitation of an electronic excited state at 10.5 eV. The model has been applied to describe the discharge and post-discharge conditions typically met in an atmospheric-pressure dielectric barrier discharge (DBD) and in a moderate-pressure microwave discharge. The reported results show the strong coupling between the excited state and the electron energy distribution kinetics due to superelastic (vibrational and electronic) collisions. Moreover, the dissociation rate from a pure vibrational mechanism can become competitive with the corresponding rate from the direct electron impact mechanism at high values of vibrational temperature.